Responding to uncertain conditions : new research on strategic adaptation - Andersen, Torben Juul (Emerald studies in global strategic responsiveness., 2023)
"The global business environment is highly uncertain, fractured by unforeseen events and making decisions that deal with a largely unknown future - organizations must improve their ability to respond. This volume of articles presents a new set of studies that attempt to better understand and address this very need."